2016
DOI: 10.1039/c6ta04898f
|View full text |Cite
|
Sign up to set email alerts
|

A new class of epitaxial porphyrin metal–organic framework thin films with extremely high photocarrier generation efficiency: promising materials for all-solid-state solar cells

Abstract: A new class of epitaxial porphyrin metal–organic framework thin films were fabricated and demonstrated to be promising materials for all-solid-state solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 58 publications
2
65
0
1
Order By: Relevance
“…high porosity and tunability, MOFs have emerged as a class of promising materials with regards to applications in gas storage/separation, 8 luminescence, 9 sensing, 10 drug delivery, 11 catalysis, 12,13 and photoelectric conversion. 14,15 The encapsulation of metal nanoparticles (MNPs) into MOFs has been demonstrated to be an efficient method to impede MNP aggregation and benet from their activity for heterogeneous catalysis. 16,17 Among the well-established methods for fabrication of MNPs@MOFs, such as incipient wetness inltration, 18 and double solvent method, 19 direct diffusion/ adsorption of the volatile metal precursors into MOFs cavities is considered as one of the most appropriate strategies for fabrication of MNPs@MOF composites.…”
Section: Introductionmentioning
confidence: 99%
“…high porosity and tunability, MOFs have emerged as a class of promising materials with regards to applications in gas storage/separation, 8 luminescence, 9 sensing, 10 drug delivery, 11 catalysis, 12,13 and photoelectric conversion. 14,15 The encapsulation of metal nanoparticles (MNPs) into MOFs has been demonstrated to be an efficient method to impede MNP aggregation and benet from their activity for heterogeneous catalysis. 16,17 Among the well-established methods for fabrication of MNPs@MOFs, such as incipient wetness inltration, 18 and double solvent method, 19 direct diffusion/ adsorption of the volatile metal precursors into MOFs cavities is considered as one of the most appropriate strategies for fabrication of MNPs@MOF composites.…”
Section: Introductionmentioning
confidence: 99%
“…Using PDFT band structure with PBE functional [45] its was shown that a small dispersion of occupied and unoccupied bands in the Г-Z direction [57], which is the porphyrin stacking direction, leads to the formation of a small indirect band gap. In a follow up study [58], the effect of introducing an electron-donating diphenylamine (DPA) into Zn SURMOFs was studied and PDFT simulations showed that DPA causes a shift in the charge localization pattern in the valence band minimum. This charge shift was PDFT calculations of porphyrin based SURMOFs has been reported by Liu et al [57,58], who studied the photophysical properties of Zn(II)porphyrin-based SURMOFs.…”
Section: Porphyrins In Organic Frameworkmentioning
confidence: 99%
“…In a follow up study [58], the effect of introducing an electron-donating diphenylamine (DPA) into Zn SURMOFs was studied and PDFT simulations showed that DPA causes a shift in the charge localization pattern in the valence band minimum. This charge shift was PDFT calculations of porphyrin based SURMOFs has been reported by Liu et al [57,58], who studied the photophysical properties of Zn(II)porphyrin-based SURMOFs. Using PDFT band structure with PBE functional [45] its was shown that a small dispersion of occupied and unoccupied bands in the Γ-Z direction [57], which is the porphyrin stacking direction, leads to the formation of a small indirect band gap.…”
Section: Porphyrins In Organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and coworkers fabricated the prototype organic photovoltaic device (Figure ) based on the oriented crystalline porphyrin film fabricated by liquid‐phase epitaxy method . Since the thin film is highly porous, ordered and oriented, it reveals a small dispersion of occupied and unoccupied bands leading to the formation of a small indirect band gap which can substantially improve device performance (Indirect band gaps support fast and highly efficient charge separation and strongly suppress charge‐carrier recombination).…”
Section: The Applications Of Crystalline Highly Oriented Mof Filmsmentioning
confidence: 99%